Crustal thickness anomalies in the Indian Ocean inferred from gravity analysis. (8th March 2016) - Suo, Yanhui; Li, Sanzhong; Li, Xiyao; Guo, Lingli; Wang, Yongming
Abstract: Oceanic crustal thickness is a critical parameter for understanding the magmatic, tectonic and hydrothermal processes at mid‐ocean ridges. Gravity anomalies can be mapped across the oceans through satellite altimetry, and these data hold valuable information about the nature and spatial variation of oceanic crust. Residual mantle Bouguer anomaly (RMBA) reflects variations in crustal thickness and crustal and mantle densities. It was simply treated as an upper mantle gravity component and a crustal gravity component in our model of a lithospheric depth. The upper mantle gravity component results from variations in mantle temperature, mantle porosity and mantle depletion due to partial melting initiating at depths of 80–100 km. The crustal gravity component results from variations in crustal thickness. RMBA contributed by mantle temperature variation of 200 K, mantle depletion of 5% and mantle porosity of 5% are 46, 16 and 21 mGal, respectively. Upper mantle gravity variations do not exceed 46 mGal, and variations in oceanic crustal thickness or deeper mantle effects have to be considered for areas with RMBA variations greater than 46 mGal. Assuming a standard RMBA of a reference crust is 0 mGal, we partitioned the RMBA in the Indian Ocean into three categories: 'negative' (less than −46 mGal), 'normal' (between −46 and 46 mGal) and 'positive' (>46 mGal), corresponding to thick, normal and thin oceanic crust, respectively. Thick oceanic crustal anomalies are associated with hotspots or plumes and are distributed along hotspot tracks. Prominent thin oceanic crustal anomalies are observed along fracture zones, around Rodriguez Triple Junction (RTJ) and Australian‐Antarctic Discordance (AAD). Besides the possible effects of fracture zones, oceanic core complex or some other enigmatic deep mantle factors must be responsible for the positive gravity anomalies and crustal thinning. Copyright © 2016 John Wiley & Sons, Ltd.